Differential Timing of Arousals in Obstructive and Central Sleep Apnea in Patients with Heart Failure - Simms, Taryn (American Academy of Sleep Medicine, 2013)
STUDY OBJECTIVES: In obstructive sleep apnea (OSA), arousals generally occur at apnea termination and help restore airflow. However, timing of arousals in central sleep apnea (CSA) has not been objectively quantified, and since arousals can persist even when CSA is alleviated, may not play the same defensive role as they do in OSA. We hypothesized that arousals following central events would occur longer after event termination than following obstructive events and would be related to circulation time. METHODS: We examined polysomnograms from 20 patients with heart failure (HF) (left ventricular ejection fraction ≤ 45%): 10 with OSA and 10 with CSA (apneahypopnea index ≥ 15). Twenty central or obstructive apneas or hypopneas were analyzed in each patient. RESULTS: Compared to the OSA group in whom arousals generally occurred at obstructive event termination, in the CSA group they occurred longer after central event termination (0.9 ± 1.1 versus 8.0 ± 4.1 s, p < 0.0001), but before peak hyperpnea. Time from arousal to peak hyperpnea did not differ between groups (4.3 ± 1.1 vs 4.8 ± 1.6 s, p = 0.416). Unlike the OSA group, latency from apnea termination to arousal correlated with circulation time in the CSA group (r = 0.793, p = 0.006). CONCLUSIONS: In HF patients with CSA, apnea-to-arousal latency is longer than in those with OSA, and arousals usually follow resumption of airflow. These observations provide evidence that arousals are less likely to act as a protective mechanism to facilitate resumption of airflow following apneas in CSA than in OSA. CITATION: Simms T; Brijbassi M; Montemurro LT; Bradley TD. Differential timing of arousals in obstructive and central sleep apnea in patients with heart failure. J Clin Sleep Med 2013;9(8):773-779.